Clinical impact of factor V Leiden, prothrombin G20210A, and MTHFR C677T mutations among sickle cell disease patients of Central India - Nishank, Sudhansu Sekhar; Singh, Mendi Prema Shyam Sunder; Yadav, Rajiv (European journal of haematology, 2013)
Background It is known that patients with sickle cell disease (SCD) present activation of the blood coagulation and fibrinolytic systems, especially during vaso‐occlusive crises and also during the steady state of the disease. We determined whether the presence of the factor prothrombin gene G20210A variant, factor V gene G1691A mutation (factor V Leiden), and methylenetetrahydrofolate reductase (MTHFR) C677T polymorphisms may be risk factors for vascular complications in individuals with SCD. Methods The study involved 150 patients with sickle cell anemia and 150 healthy controls of Central India. Genotyping of three thrombophilic mutations was carried out by PCR‐RFLP methods using MnlI, Hind III, and Hinf I, respectively, for factor V Leiden, prothrombin, and MTHFR mutations. Results Patients with SCD had significantly higher prevalence of mutant variants of MTHFR gene (28.0% heterozygotes and 14.6% homozygotes) and FVL gene (14.6% heterozygotes) as compared to normal/control individuals, but complete absence of mutant variants of prothrombin gene. The patients with SCD having mutant variants of MTHFR and FVL genes showed higher incidence of pain in chest, abdomen, and bone joints along with early age of onset of clinical manifestations as well as frequent dependence on blood transfusion than those patients with SCD having wild variants of these thrombotic genes. As compared to control subjects, SCD individuals having mutant variants of FVL and MTHFR genes had significant association with higher levels of prothrombin fragment (F1+2), D‐dimer, thrombin‐antithrombin (TAT), and lower level of protein C. Conclusion MTHFR C677T and FVL G1691A polymorphisms may be risk factors for increased vascular complications in patient with SCD.